Generation of a database of mass spectra patterns of selected Mycobacterium species using MALDI-ToF mass spectrometry - Oduwole, Elizabeth O. (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScMedSc (Pathology. Medical Microbiology))--Stellenbosch University, 2008.